Histopathology of tick-bite lesions in naturally infested capybaras (Hydrochoerus hydrochaeris) in Brazil - Van Der Heijden, K. M.; Szabo, MPJ; Egami, M. I.; Pereira, M. C.; Matushima, E. R. (Springer, 2005)
In the present work features of tick-bite lesions were evaluated in capybaras naturally infested with Amblyomma cajennense and Amblyomma dubitatum ticks. Gross appearance of tick bite site was characterized by a mild swelling and erythema. Microscopic examination revealed the cement cone, a tube-like homogenous eosinophilic mass penetrating deep into the dermis. This structure was surrounded in the dermis by a cellular infiltrate and free eosinophilic granules and was associated to edema of variable intensity. Necrosis was a common feature deep in the dermis particularly at the far end of the eosinophilic tube. Hyperplasia, cellular edema and occasionally necrosis of keratinocytes could be seen at both sides of the ruptured epidermis. Cellular infiltrate was constituted overwhelmingly by polymorphonuclear leukocytes with eosinophilic granules. In capybaras cells with such features can be either eosinophils or heterophils (pseudoeosinophils), the latter being the equivalent of neutrophils of other mammals. Ultrastructural analysis of the cellular infiltrate revealed the predominance of heterophils over eosinophils. Mononuclear cells and mast cells and, in lesser numbers, basophils were also seen at skin attachment sites. The presence of heterophils in the reaction of capybaras against Amblyomma ticks is an outstanding feature but its role in the reaction to the tick is not known. It is however speculated that capybara heterophils might be associated with a more permissive environment for tick feeding and pathogen transmission as already shown for the equivalent cell type, the neutrophil, in the reaction of the dog against the Rhipicephalus sanguineus tick.
Keywords: capybara; heterophils; histopathology; ixodidae; ticks